Pengaruh Edukasi Pendidikan Gizi Terhadap Perilaku Anak Sekolah Kelas V di SDS IT Al Wahdah Kendari Tahun 2024 - Nabila Dwi Saputri; Hartati Bahar; Hariati Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Multiple nutrition is still a major problem for most Indonesians, including school-age children, which affects the quality of human resources. School-age children are a nutritionally vulnerable group that requires a diverse food intake to support rapid growth and development. This study aims to determine the effect of nutrition education on behavior (knowledge, attitude, motivation and action) of fifth grade school children through the book media “My Nutrition Diary.” at SDS IT Al Wahdah Kendari in 2024. The type of research used is Pre-experimental with One Group Pre test - Post test Design. The population of this study were fifth grade students of SDS IT Al Wahdah Kendari Year 2024 totaling 54 people, the sampling technique was purposive sampling with a sample size of 35 respondents. Data collection using a questionnaire given to respondents before and after being given education with promotional media for my nutrition diary. Data analysis using paired test. The results of the study, there is an effect of education with the media promotion of my nutrition diary book given by students to increase students' knowledge, attitudes, motivation and actions about balanced nutrition, namely knowledge p value (0.000) < ? (0.05), attitude p value (0.000) < ? (0.05), student motivation p value (0.000) < ? (0.05). and student action p value (0.000) < ? (0.05).